Single-cell RNA sequencing reveals cancer stem-like cells and dynamics in tumor microenvironment during cholangiocarcinoma progression - Golino, Jihye L.; Bian, Jing; Wang, Xin; Fu, Jianyang; Zhu, Xiao Bin; Yeo, Julie; Kelly, Michael; Escorcia, Freddy E.; Cam, Maggie; Xie, Changqing (Frontiers in Cell and Developmental Biology, 2023)
Cholangiocarcinoma is a malignancy of the bile ducts that is driven by the activities of cancer stemlike cells and characterized by a heterogeneous tumor microenvironment. To better understand the transcriptional profiles of cancer stem-like cells and dynamics in the tumor microenvironment during the progression of cholangiocarcinoma, we performed single cell RNA analysis on cells collected from three different timepoints of tumorigenesis in YAP/AKT mice model. Bulk RNA sequencing data from TCGA and ICGC cohort were used to verify and support the finding. In vitro and in vivo experiments were used to assess the stemness of cancer stem-like cells. We identified Tm4sf1high malignant cells as cancer stem-like cells. Across timepoints of cholangiocarcinoma formation in YAP/AKT mice, we found dynamic change of cancer stem-like cell/stromal/immune cell composition, Nevertheless, the dynamic interaction among cancer stem-like cells, immune and stromal cells at different timepoint was elaborated. Collectively, these data serve as a useful resource to better understanding cancer stem-like cell and malignant cell heterogeneity, the stromal cell remodeling and immune cell reprogram. It also sheds new light on transcriptomic dynamics during the cholangiocarcinoma progression at single-cell resolution.